The Spread of Deepfakes in Digital Networks - Tonello, Tommaso; Dimitrova, Aseniya; Fenga, Livio; Biazzo, Luca; Jacona, Alessio (Deepfakes, Democracy, and the Ethics of Synthetic Media: A Synthesis of the SOLARIS Project, 2026)
This chapter explores the spread of deepfakes through social media platforms (e.g. X, Facebook and TikTok). By studying real-world case studies, such as political deepfakes or celebrity impersonations, the chapter illustrates how synthetic media exploit online engagement dynamics to reach massive audiences quickly. It then reviews current methods used to detect and track deepfakes, especially early-warning systems monitoring content spread patterns to flag potential deepfakes in real time, as well as novel research instruments developed as part of the SOLARIS project. The chapter then presents the role of traditional media in debunking and contextualising deepfakes, reflecting upon the challenges that AI-generated disinformation poses to journalists and media professionals. In this context, insights from SOLARIS’ Use Case 2 are used to show how targeted interventions can slow the spread of harmful synthetic media. Finally, the chapter advocates for bottom-up AI education to frame digital citizens’ needs and to foster their ability to engage with online synthetic content.